Dam methylation regulates the expression of SPI-5-encoded sopB gene in Salmonella enterica serovar Typhimurium - Giacomodonato, Mónica Nancy (2014)
DNA adenine methylation is an essential factor in Salmonella virulence. Here, we investigate the involvement of DNA adenine methylase (Dam) in the expression and translocation of a SPI-5-encoded effector of S. Typhimurium. SopB expression and secretion were determined using SopB–FLAG-tagged wild type and dam strains of S. Typhimurium. Western blot and quantitative reverse transcriptase PCR analysis showed that the dam mutant expresses lower levels of SopB protein and sopB mRNA than the wild type strain under SPI-1 and SPI-2 inducing conditions in vitro. SopB secretion was also considerably impaired in the absence of dam. In agreement with in vitro experiments, SopB synthesis in dam mutants recovered from infected epithelial cells and from murine mesenteric lymph nodes was reduced by 40% respect to the wild type strain (p < 0.05). SopB translocation was neither detected in the cytosol of epithelial cells nor in the cytosol of cells isolated from mesenteric lymph nodes infected with the dam mutant. Taken together, our results demonstrate that, in S. Typhimurium, Dam methylation modulates the expression and translocation of SPI-5-encoded SopB effector.